Analysis of Transient Voltage Stability in a Low Voltage Distribution Network Using SST for the Integration of Distributed Generations - Sheng Li; Zhihao Zhou; Qiqi Shan; Jiani An (Journal of Electrical and Computer Engineering)
Models of a low voltage distribution network using a typical tertiary-structure solid state transformer (SST) for the integration of distributed generations (DGs) and a conventional low voltage distribution network integrated with DGs were established to study the transient voltage stability issue, using the power system simulation software PSCAD. Effects on the transient voltage stability of the load bus and DC bus in the SST system are analyzed when grid-side cable line faults (such as short circuit and line disconnection) occur or the total output of DGs drops greatly. The results show that, comparing with the conventional system, the SST has apparent advantages on enhancing the transient voltage stability of load bus while facing different disturbances, even though SST has to regulate the voltage passively. Short circuit faults at different location of the grid-side line have different effects on the transient voltage stability, while the effect of disconnection fault is not related to fault location. Moreover, the DC bus voltage is easy to keep climbing continually when short circuit fault of the line occurs that is close to the SST input stage or disconnection fault occurs at any location of the line. If a battery energy storage station is installed, the transient voltage stability of DC bus and load bus will be improved effectively because of the regulation function of battery storage.